The European Union and Its Neighbours. A legal appraisal of the EU’s Policies of stabilisation, partnership and integration, ed. by Steven Blockmans and Adam Łazowski, The Hague 2006 - Piskorska, Beata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Recenzja: The European Union and Its Neighbours. A legal appraisal of the EU’s Policies of stabilisation, partnership and integration, ed. by Steven Blockmans and Adam Łazowski, The Hague 2006.